Augustine's Time of Death in "City of God" 13 - Hannan, Sean (Augustinian studies, 2019)
"Only a living person can be a dying one," writes Augustine in De ciuitate dei 13.9. For Augustine, this strange fact offers us an occasion for reflection. If we are indeed racing toward the end on a cursus ad mortem, when do we pass the finish line? A living person is "in life" (in uita), while a dead one is post mortem. But as ciu. 13.11 asks: is anyone ever in morte, "in death?" This question must be asked alongside an earlier one, which had motivated Augustine's struggle in Confessiones 11.14.17 to make sense of time from the very beginning: quid est enim tempus? What is at stake here is whether or not there is such a thing as an instant of death: a moment when someone is no longer alive but not yet dead, a moment when they are "dying" (moriens) in the present tense. If we want to understand Augustine's question about the time of death in ciu. 13, then we have to frame it in terms of the interrogation of time proper in conf. 11.